Zen of Cloud Learning Cloud Computing by Examples on Microsoft Azure - Bai, Haishi (CRC Press, 2014)
CLOUD COMPUTING FUNDAMENTALSOverview of Cloud ComputingHistoryEssence of Cloud Computing     Elasticity          On and Off Mode          Rapid-Growth Mode     Availability          Fault Domain          Update Domain     ScalabilityMicrosoft Azure Overview     IaaS (Infrastructure as a Service)     PaaS (Platform as a Service)     SaaS (Software as a Service)     Cost CalculationPreparing the Development Environment for Microsoft Azure     Subscribe to Microsoft Azure     Install Software Development KitIntroduction of Microsoft Azure Management Portal     Sign In     Page